2009
DOI: 10.1007/s00520-009-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and implications of cancer patients’ psychosocial needs

Abstract: Almost a third of the cancer patient population indicates an unmet need for psychosocial support or is actually using psychosocial services. Emotional functioning is a central predictor of the requirement for psychosocial support. Women are emotionally more affected than men and need more psychosocial support. The prognostic validity of the severity of depression and anxiety is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 45 publications
6
54
1
8
Order By: Relevance
“…Fifty enough support, with 58% of the support provided by family and friends, while 42% of the support came from the health-care team. Many studies have shown the need for the cancer patient to receive psychological support (Ernstmann et al, 2009;Goldzweig et al, 2010). In a German study, 18.9% of patients indicated an unmet need for psychosocial support and 9.5% of patients were actually using psychosocial services; that need was higher in female patients (Merckaert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty enough support, with 58% of the support provided by family and friends, while 42% of the support came from the health-care team. Many studies have shown the need for the cancer patient to receive psychological support (Ernstmann et al, 2009;Goldzweig et al, 2010). In a German study, 18.9% of patients indicated an unmet need for psychosocial support and 9.5% of patients were actually using psychosocial services; that need was higher in female patients (Merckaert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Gender, emotional functioning (Ernstmann et al, 2009), age and time since diagnosis (Sanson-Fisher et al, 2000) are factors that earlier have been associated with enhanced psychosocial or supportive care needs for patients with cancer. However, factors or characteristics that may impact the need of supportive care within this patient group needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Natürlich ist hier zu berück-sichtigen, dass die Teilnehmer an der Gruppenevaluationsstudie wussten, dass sie randomisiert würden, was möglicherweise die Teilnahmebereitschaft negativ beeinflusst hat. Teilnehmer an der Gruppenevaluationsstudie waren signifikant jünger als die bei- (Ernstmann et al 2009;Tuinman et al 2015), trotz dieses alters-und geschlechtsspezifischen Angebotes.…”
Section: Diskussionunclassified